Spectroscopic characterization of SnO2 gels - Code: CP11 - Ribeiro, Sidney J.L. [UNESP]; Santilli, Celso V. [UNESP]; Pulcinelli, Sandra H. [UNESP]; Fortes, Fábio L. [UNESP]; De Oliveira, Luiz F.C. (Springer Nature, 1994)
Excitation and dynamic emission spectra of Eu3+ ions were simultaneously used with FTIR and Raman spectroscopy to study the structural evolution during SnO2 sol → gel → xerogel conversion. Results make evident an increase of the surroundings symmetry for the Eu3+ ions dissolved in SnO2 matrix and a decrease of the amount of hydroxo groups (Sn-OH) during drying. These phenomena were associated to the pursuit of the condensation reaction after gelation. © 1994 Kluwer Academic Publishers.
Keywords: gel drying; optical spectroscopy; tin oxide hydrogel